2021
DOI: 10.1149/2162-8777/abe423
|View full text |Cite
|
Sign up to set email alerts
|

Review—Betavoltaic Cell: The Past, Present, and Future

Abstract: In recent years, betavoltaic batteries have become an ideal power source for micro electromechanical systems. Betavoltaic battery is a device that converts the decay energy of beta emitting radioisotope sources into electrical energy using transducers. They have the advantages of high energy density, long service life, strong anti-interference ability, small size, light weight, easy miniaturization and integration, thus it has become a research hotspot in the field of micro energy. However, to date, the low en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…The half-life is the period required for a quantity to reduce to half of its initial value. The equation of half-life is calculated using eqs and , , N = N 0 e λ t λ = e 0.693 t / τ where N is the number of radioisotope parent nucleus remaining from the decay, N 0 is the initial number of parent nucleus, λ is the decay constant, t is time, and τ is the half-life of the radioisotope. Since betavoltaic battery uses the β-particles emitted from the radioisotope as an energy source, the long half-life of the radioisotope provides a continuous energy supply and a long shelf life.…”
Section: Insight Into Betavoltaic Batterymentioning
confidence: 99%
See 2 more Smart Citations
“…The half-life is the period required for a quantity to reduce to half of its initial value. The equation of half-life is calculated using eqs and , , N = N 0 e λ t λ = e 0.693 t / τ where N is the number of radioisotope parent nucleus remaining from the decay, N 0 is the initial number of parent nucleus, λ is the decay constant, t is time, and τ is the half-life of the radioisotope. Since betavoltaic battery uses the β-particles emitted from the radioisotope as an energy source, the long half-life of the radioisotope provides a continuous energy supply and a long shelf life.…”
Section: Insight Into Betavoltaic Batterymentioning
confidence: 99%
“…Therefore, pure β − decaying radioisotopes are the best energy source for a betavoltaic battery. 17 Table S1 (Supporting Information) shows the commonly used pure β − decaying radioisotopes. 24,25 There are several factors to consider before choosing a radioisotope for a betavoltaic battery, such as half-life, decay energy of the radiation (maximum and average decay radiation), and the specific power of the radioisotope.…”
Section: Selection Of β-Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…We are interested in SiC as an energy converter in photovoltaics and betavoltaics. The last direction is rapidly developing nowdays [1]. We can collect all technologies of obtaining this material in four groups.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the maximum efficiency, the short-circuit current (I SC ) and the open-circuit voltage (V OC ) of BV cell must be improved. By investigating the literature, [5][6][7][8][9][10][11][12][13][14] it was found that the parameters, such as a doping concentration and a thickness of p-, i-, n-type layers, a width of depletion region, a position of depletion region and radioisotope source, and a surface geometry, affected the I SC and V OC of BV cells. Especially, the design optimization of depletion region was very important because electron-hole pairs (EHPs) by emitting β-particles are mostly generated in depletion region.…”
Section: Introductionmentioning
confidence: 99%